Field assessment of corrosion probability in reinforced concrete structures using ASTM C876-based half-cell potential measurement in Tansen, Nepal: Research Article - Gautam, Madhab; Pandey, Barsha; Chhetri, Shristi Paudel; Gaha, Lila; Bhattarai, Nootan Prasad; Bhattarai, Jagadeesh (BIBECHANA, 2026)
The non-destructive, in-situ open-circuit potential mapping (OCPM) technique is used to investigate the corrosion probability conditions of rebar-embedded concretes (RECs) in urban areas of Tansen Municipality, Nepal. One hundred and three (103) REC samples of five different types are assessed in the present study. Corrosion condition of 51 building pillars (BPs), 27 reinforcement road slabs (R2Ss), 10 building roofs (BRs), 10 fencing pillars (FPs), and 5 sewage supply pipes (S2Ps) are evaluated from four surface points of each sample specimen per ASTM C876-22b standards. This assessment indicates the RECs of Tansen municipality areas are in a minimal or least corrosion risk (LCR) zone, i.e.,